Analysis of casesof congenital syphilisin Sobral, Ceará: contributions to pre natal care - Mesquita, Karina O.; Lima, Gleiciane Kélen; Filgueira, Adriano A.; Flôr, Sandra Maria C.; Freitas, Cibelly Aliny S.L.; Linhares, Maria Socorro C.; Gubert, Fabiane A. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: The syphilis is a chronic infectious disease, caused by the bacteria Treponema pallidum and acquired through the sexual contact. The vertical transmission, of the pregnant woman not infected treated or treated inadequately, it happens frequently, resulting in the congenital syphilis. Objective: This study had the objective of analyzing the profile of the nine cases of congenital syphilis of Sobral, Ceará, happened in 2010. Methods: It is a documental research, of the exploratory-descriptive type. The data were collected starting from the handbooks of the cases and of the System of Information of Offences of Notification. To know the tendency of the disease in the municipal district, firstly the incidence of congenital syphilis was rescued in Sobral, from 2007 to 2010. Later the data were stratified in variables and presented in the form of graphs and tables. Results: Of the nine pregnant women, seven were single, six were users of alcohol e/ou other drugs and, in agreement with the registration of the occupation, three were professional of the sex. In relation to the number of consultations accomplished in the prenatal, six accomplished the recommended total, however it was verified that the distribution of those consultations was inadequate to the age gestational. All the mothers were inadequately treated and, in the moment of the research, only a child met with the following accomplished appropriately to the protocol of ministry of Health. Conclusion: The explanation to the pregnant women about the gravity of the disease, the transmission way, the consequences for the concept and the need of treating the partner are fundamental points for the prevention of the congenital syphilis.